Chapter Biodiversity smart monitoring guided by historical analysis of coastal evolution - Geronimo, Stefania (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The present work focuses on the preparatory phase of the design of the biodiversity monitoring network. The preliminary results of this first phase are then presented, starting from the formation of a cognitive framework based on previous knowledge of environmental parameters, the definition of sampling stations, areas, and detection points. At the same time, the results of the analysis of the evolutionary dynamics of the coasts are shown in the light of the new analyses and new measures, which, together with existing data, aim to inform the monitoring strategy.